PENGARUH IKLAN DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN HANDPHONE MEREK OPPO PADA MAHASISWA UNIVERSITAS HKBP NOMMENSEN MEDAN (STUDI KASUS) - TRI MELDA MEI LIANA (LP2MTBM MAKARIOZ, 2019)
The purpose of this research is to find out the effect of advertising and brand image on the decision to buy Oppo brand mobile phones for students of HKBP Nommensen University, Medan. This type of research is a survey research with a quantitative approach. The population in this study were students who used the Oppo brand mobile phone. The sampling technique used purposive sampling, so that a total sample of 50 people was obtained. Data collection techniques were carried out using a questionnaire (list of statements), interviews (interviews), observation and documentation studies. The research instrument conducted by researchers by giving questionnaires with a Likert measurement scale of 1 to 5. The analytical methods used in this study include: Descriptive Method, Multiple Linear Regression Analysis Method, Validity Test, Reliability Test, Classical Assumption Test (Test for Normality, Test for Heteroscedasticity , Multicollinearity test), Hypothesis Test (t-test and F-test), and the coefficient of determination (R2) test. Data processing using SPSS 20.0 for windows. From the results of data analysis, we obtained the equation of multiple linear regression analysis, namely: Ŷ = 1.512 + 0.339X1 + 0.558X2. Simultaneous Test Results (F-Test) obtained Fcount of 6.202 and Ftable of 3.20, so that the value of Fcount> Ftable (6.202> 3.20) at α = 5%. And the partial test results (t-test) obtained the results of the assessment of advertising variables tcount <ttable (1.495> 1,677) means that partially there is no positive and significant influence of advertising variables on the purchase decision, tcount brand image variables> ttable (2.167> 1.677 ) means that partially there is a positive and significant influence of brand image variables on purchasing decisions. The results of the coefficient of determination (adjusted R Square) with a result of 20.9%, which means that purchasing decisions can be explained by advertising variables and brand image and the remaining 79.1% is explained by other variables outside this study